Comparison of leeching and heparin therapy in management of acute venous congestion of limbs in rat - Seyed Abdollah Mousavi; Maryam Ghasemi; Seyed Jaber Mousavi; Seyyed Saied Mousavi Darka; Vafa Bagheri (Mazandaran University of Medical Sciences, 2016)
Acute venous congestion leads to blood stasis in the tissue and impaired blood perfusion. Using medicinal leech is an old method for reducing tissue congestion. There are numerous factors in leech saliva and hirudin that have important roles in the leeching beneficial effect. In this study, an animal study was performed to compare leech therapy with heparin therapy in the treatment of acute venous congestion. Thirty male rats were divided into three groups. In the first group, an acute venous congestion was induced at the thigh. Decongestion was performed through the touch of hirudo medicinalis leech. In the second group, heparin sodium was injected, after tourniquet removal. Eventually, no treatment or procedure was performed in the third group after opening of tourniquet. Histopathological and biochemical analysis were performed in these rat. Edema size in heparin therapy and control groups was significantly greater than leech therapy group. Creatine phosphokinase blood level in leech therapy group was significantly lower than the control group, but this difference was unobserved between heparin therapy and control. In contrast, the level of lactate dehydrogenase and aldolase greatly increased in the control group, which received no intervention. Also in histopathological assessment, the level of tissue damage in both heparin and leech therapy groups showed a significant decrease as compared to the control group. Leech therapy can probably be more effective in the reducing of cellular damage caused by acute tissue congestion as compare to heparin therapy.